Hubungan dukungan sosial dengan kualitas hidup penderita HIV/AIDS di Yogyakarta - Annike Ayu Maulita; Suratini Suratini (THE JOURNAL OF Mother and Child Health Concerns, 2022)
Background: HIV-AIDS is a chronic and progressive disease that can impact all aspects of life physically, psychologically, socially or spiritually. Problems that arise due to disease, stigma, discrimination, will reduce the quality of life of PLHIV. One of the factors that can overcome the life problems of sufferers is to provide social support. Social support can help overcome PLWHA problems both physically and psychologically. The existence of support from the social environment makes PLWHA have help with the problems they face to improve their quality of life. Purpose: To find out the relationship between social support and the quality of life of people with HIV-AIDS. Method: This type of research is descriptive correlation with a cross sectional approach. The research subjects were PLWHA at the Victory Plus Yogyakarta Foundation, aged 20-45 years, totaling 31 respondents who were taken using the non-probability sampling technique with the accidental sampling method. The measuring instrument in this study used a questionnaire, while the hypothesis analysis used the Sperm Rank correlation test. Results: Data analysis using Sperman rank showed a value (p-value 0.00, p.0.05) with a correlation coefficient (r) of 0.692 indicating a strong relationship. Conclusion: There is a relationship between social support and the quality of life of HIV-AIDS sufferers with a strong correlation with a correlation value (r) of 0.692. Suggestion: For families to provide social support to PLWHA to improve the quality of life for people with HIV-AIDS.   Pendahuluan: Penyakit HIV-AIDS yang bersifat kronis dan progresif dapat berdampak pada segala aspek kehidupan baik secara fisik, psikologis, sosial, atau spiritual. Permasalahan yang timbul akibat penyakit, adanya stigma, diskriminasi, akan menyebabkan penurunan kualitas hidup ODHA. Salah satu faktor yang dapat mengatasi permasalahan hidup penderita adalah dengan memberikan dukungan sosial. Dukungan sosial dapat membantu mengatasi masalah ODHA baik secara fisik atau psikologis. Adanya dukungan dari lingkungan sosial menjadikan ODHA memiliki pertolongan terhadap masalah yang dihadapi meningkatkan kualitas hidupnya. Tujuan: Untuk mengetahui hubungan dukungan sosial dengan kualitas hidup penderita HIV-AIDS. Metode: Jenis penelitian Deskriptif korelasi dengan pendekatan cross sectional. Subjek penelitian adalah ODHA di Yayasan Victory Plus Yogyakarta yang berusia 20-45 tahun berjumlah 31 responden yang diambil dengan menggunakan teknik Non probability sampling dengan metode accidental sampling. Alat ukur pada penelitian ini menggunakan kuesioner, sedangkan analisa hipotesis menggunakan uji korelasi Sperman Rank. Hasil: Analisis data dengan sperman rank menunjukkan nilai (p-value 0,00, p,0,05) dengan koefisiensi korelasi (r) sebesar 0,692 menunjukkan keeratan hubungan kuat. Simpulan: Terdapat hubungan dukungan sosial dengan kualitas hidup penderita HIV- AIDS dengan keeratan hubungan hubungan  kuat dengan nilai korelasi (r) sebesar 0,692. Saran: Agar keluarga memberikan dukungan sosial pada ODHA untuk meningkatkan kualitas hidup penderita HIV-AIDS.